IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) BERBANTUAN E-LKM UNTUK MENINGKATKAN MOTIVASI BELAJAR MURID SMP - Aura Yuan Risky, Citra; Astriani, Dyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ learning motivation in science learning is still relatively low because the learning process tends to be teacher-centered and lacks the use of interactive learning media. This study aims to describe the implementation of learning, analyze the improvement of students’ learning motivation, and determine students’ responses after the implementation of the Think Pair Share (TPS) cooperative learning model assisted by E-LKM. This research used a pre-experimental method with a One Group Pretest–Posttest design. The instruments included a learning implementation observation sheet, a students’ learning motivation questionnaire, and a students’ response questionnaire. Data were analyzed using percentage analysis and the N-Gain test based on the ARCS indicators (attention, relevance, confidence, and satisfaction). The results showed that the learning implementation was categorized as very good with percentages ranging from 92% to 100%. The average N-Gain score was 0.70 (moderate category), and students’ responses were very positive with an average percentage of 85%. These results indicate that the TPS model assisted by E-LKM can improve students’ learning motivation in science learning.